Tax Law Enforcement in Indonesia: Administrative vs Criminal Sanctions - Eka Putra, Fariz; Suseno, Sigid; Santoso, Topo; Muttaqin, Zainal (Jambe Law Journal, 2025)
Legal issues arising from violations of tax provisions are resolved through administrative law mechanisms. Tax legislation grants the state broad authority to collect taxes, making tax law a part of public law, and regulating the legal relationship between the state and individuals or legal entities obligated to pay taxes. The existence of criminal provisions in Tax Legislation, called administrative penal law (Verwaltungs Strafrecht), which is included in the framework of public welfare offenses (Ordnungswidrigkeiten), is defined as all legislative products in the form of laws within the administrative sphere that have criminal sanctions. In cases of tax crimes experienced by taxpayers who have been sentenced to criminal penalties, the convict (taxpayer) is still required to pay his tax administration obligations, resulting in the imposition of double sanctions (criminal and administrative) for the same act (double sanction) which is contrary to legal certainty and a sense of justice, and is not in line with the ratio legis of the Taxation Law. As a doctrinal legal research, this article investigates how the administrative and criminal sanctions are applied in taxation in Indonesia and how legal certainty is guaranteed in the tax law. It is found that criminal and administrative sanctions are applied according to the actions taken based on the qualifications outlined in the articles violated. The procedure for enforcing tax law varies and is applied on a case-by-case basis. Further, administrative sanctions are the precursor to criminal sanctions. While administrative sanctions are the primum remedium applied in tax administration violations, which are carried out to obtain payment, criminal tax sanctions are applied as the ultimum remedium, taking into account the objective conditions related to the act